AS MARCAS DO CÁRCERE: 5 ANOS - Ayres França, Leandro; Ramos Artuso, Alysson (Novos Estudos Jurídicos, 2021)
Resenha de: FRANÇA, Leandro Ayres; STEFFEN NETO, Alfredo; ARTUSO, Alysson Ramos. As marcas do cárcere. Curitiba: iEA Sociedade, 2016. ISBN 978-85-67644-13-4.